2006
DOI: 10.1002/bit.20907
|View full text |Cite
|
Sign up to set email alerts
|

Controlling light-use byRhodobacter capsulatus continuous cultures in a flat-panel photobioreactor

Abstract: The main bottleneck in scale-up of phototrophic fermentation is the low efficiency of light energy conversion to the desired product, which is caused by an excessive dissipation of light energy to heat. The photoheterotrophic formation of hydrogen from acetate and light energy by the microorganism Rhodobacter capsulatus NCIMB 11773 was chosen as a case study in this work. A light energy balance was set up, in which the total bacterial light energy absorption is split up and attributed to its destinations. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 34 publications
0
35
0
Order By: Relevance
“…Process intensification is required to overcome the problem of light delivery to the second stage photofermentations, which would push bio-H 2 production to competitive levels. A review of photobioreactor designs to achieve effective light transfer into high-activity cultures is outside the scope of this overview; the reader is referred to recent reviews (Tsygankov 2001;Hoekema et al 2002;Kondo et al 2002;Hoekema et al 2006;. (Zhu et al 2002) NG: The productivity of carbohydrate accumulation was not given and could not be calculated from given data.…”
Section: : Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Process intensification is required to overcome the problem of light delivery to the second stage photofermentations, which would push bio-H 2 production to competitive levels. A review of photobioreactor designs to achieve effective light transfer into high-activity cultures is outside the scope of this overview; the reader is referred to recent reviews (Tsygankov 2001;Hoekema et al 2002;Kondo et al 2002;Hoekema et al 2006;. (Zhu et al 2002) NG: The productivity of carbohydrate accumulation was not given and could not be calculated from given data.…”
Section: : Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Generally, higher light conversion efficiencies were obtained at low light intensities [56]. Light conversion efficiency reduced from 1.11% to 0.25% as the light intensity increased from 88 to 405 W/m 2 [62].…”
Section: Light Distributionmentioning
confidence: 89%
“…These enzymatic processes rely on chemical bond energy (ATP) [25] generated by the conversion of absorbed light energy to ATP as discussed in Section 3. This energy is utilized in different basic cellular metabolic activities such as biomass formation, biomass maintenance, hydrogen production and the excess is dissipated as heat [4,56]. Indoor studies have demonstrated…”
Section: Effects Of the Variation In Solar Light Intensity And Tempermentioning
confidence: 99%
See 1 more Smart Citation
“…Wijffels and colleagues first used the De-stat approach for optimizing the photosynthetic efficiency of the purple nonsulphur bacterium Rhodobacter capsulatus for the production of hydrogen from acetate and light energy by determining important components of the light energy balance: biomass growth and maintenance, generation of hydrogen, and photosynthetic heat dissipation (Hoekema et al, 2006). They saw that culture characteristics were strongly dependent on m.…”
Section: Deceleration-stat (De-stat)mentioning
confidence: 99%